Do Higher State Minimum Wages Reduce the Racial Wage Gap for Men? - Gabriel, Paul E.; Schmitz, Susanne (Journal of Applied Business and Economics, 2023)
Using data from the 2019 Current Population Survey, we find that black, non-Hispanic men who reside in states with the highest minimum wages (above 10 in 2018) have a slightly smaller wage gap relative to white, non-Hispanic men. However, wage regressions show no appreciable improvement in the relative earnings of black men in states with minimum wages that exceed the federal level when accounting for other demographic determinants of earnings. Our results indicate that increasing a state’s minimum wage does not appear to be an effective policy tool to reduce racial wage inequality for men.